2018
DOI: 10.21873/anticanres.12679
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Exosomes Derived from Chronic Myelogenous Leukaemia Cells as a Biomarker

Abstract: CML-derived exosomes could act as novel targets for the detection of the BCR-ABL transcript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 27 publications
0
32
1
Order By: Relevance
“…1 monitored from diagnosis to the achievement of the dMR) the exosome enrichment performed using the SoRTEV™ EV-RNA Low Volume Enrichment kit highlighted the presence of the BCR-ABL1 transcript in leukemia-derived EVs. A previous study demonstrated the detectability of this fusion gene transcript in the total exosomes pool of patients affected by cML, not enriched for specific sub-populations; BCR-ABL1 was only detected by conventional nested PcR in patients in the accelerated phase or in blast crisis (44). These results contradict those of the present study, which may be due to the improvements in the specificity of leukemia-derived exosome enrichment methods combined with highly sensitive dPCR quantification.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…1 monitored from diagnosis to the achievement of the dMR) the exosome enrichment performed using the SoRTEV™ EV-RNA Low Volume Enrichment kit highlighted the presence of the BCR-ABL1 transcript in leukemia-derived EVs. A previous study demonstrated the detectability of this fusion gene transcript in the total exosomes pool of patients affected by cML, not enriched for specific sub-populations; BCR-ABL1 was only detected by conventional nested PcR in patients in the accelerated phase or in blast crisis (44). These results contradict those of the present study, which may be due to the improvements in the specificity of leukemia-derived exosome enrichment methods combined with highly sensitive dPCR quantification.…”
Section: Discussioncontrasting
confidence: 99%
“…Specifically, a previous study demonstrated the possibility of quantifying the BCR-ABL1 transcript in exosomes isolated from the PB of patients with cML in advanced disease phases, such as accelerating or blast phases. However, they were not be able to detect BCR-ABL1 by nested PcR in cML patients in the cP (44).…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, changes in absolute EV counts and EV protein contents have been observed after induction chemotherapy and corresponded to blast reduction in the BM (117,119). Furthermore, EVs from malignant cells express abundant surface proteins unique to their cell of origin (120). For example, EVs derived from multiple myeloma cells overexpress, on their cell membrane, proteins such as CD147, CD38, and CD138 (115,(121)(122)(123).…”
Section: Ev Applications In Promoting Gvl and In Preventing Disease Rmentioning
confidence: 99%
“…Accessible, reliable, and informative hematological malignancies biomarkers can be medically valuable and can provide some relevant insights into cancer biology [Elsherbini and Bieberich., 2018]. Early detection of cancer could be easily performed using exosomes isolated from body fl uids such as blood plasma, serum, and urine, which is allowing for a non-invasive method of detection of hematological malignancies, (Kang et al, 2018).…”
Section: The Role Of Exosomes In Diagnosis and Prognosis Of Hematologmentioning
confidence: 99%
“…Microvesicles are found in higher concentrations in the sera of different types of hematological malignancies, such as AML, AL L, CML, CLL, diffuse large B-cell lymphoma ( DLBCL), Hodgkin's lymphoma (HL) and MM patients and abundantly express surface proteins unique to their cell of origin, which is rarely observed from serum microvesicles of normal controls [Kang et al, 2018]. AML biomarkers NPM1, FLT3, CXCR4, MMP9 and IGF-IR are also present in AML cell derived exosomes, along with mRNAs involved in leukemia development (Boyiadzis, 2016).…”
Section: The Role Of Exosomes In Diagnosis and Prognosis Of Hematologmentioning
confidence: 99%